2020
DOI: 10.1016/j.jaci.2020.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Complement activation in patients with COVID-19: A novel therapeutic target

Abstract: Disclosure of potential conflict of interest: R. Caorsi receives speaker's fees and has consultancies for Novartis and SOBI. A. Ravelli receives speaker's fees and has consultancies for Novartis and SOBI. M. Gattorno receives speaker's fees and has consultancies for Novartis and SOBI. The rest of the authors declare that they have no relevant conflicts of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
237
2
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(271 citation statements)
references
References 9 publications
22
237
2
10
Order By: Relevance
“…21 In particular, complement may be involved in coronavirus pathogenesis, as inferred from the finding that C3 knockout mice infected with SARS-CoV have less lung disease than wild-type mice. 22 Preliminary data provide evidence for activation of complement (sC5b-9 and C5a) in patients with COVID-19, with significantly higher plasma levels in the patients with severe disease than in those with moderate disease. Hence, complement activation has been suggested as a novel therapeutic target in COVID-19.…”
Section: F I G U R Ementioning
confidence: 82%
“…21 In particular, complement may be involved in coronavirus pathogenesis, as inferred from the finding that C3 knockout mice infected with SARS-CoV have less lung disease than wild-type mice. 22 Preliminary data provide evidence for activation of complement (sC5b-9 and C5a) in patients with COVID-19, with significantly higher plasma levels in the patients with severe disease than in those with moderate disease. Hence, complement activation has been suggested as a novel therapeutic target in COVID-19.…”
Section: F I G U R Ementioning
confidence: 82%
“…A total of 777 records were collected by the databases and manual searching. After the exclusion of the duplicates, review articles, case reports, pre‐printed versions without peer‐review, and irrelevant studies by title or abstract screening, 187 studies remained for full‐text review; 52 studies 6,17‐67 were finally included into the meta‐analysis, and 18 studies were included in the qualitative synthesis (Figure 1). A total of 52 records involving 10 614 COVID‐19 patients confirmed between December 25, 2019, and June 1, 2020, were included.…”
Section: Resultsmentioning
confidence: 99%
“…Our study shows evidence of complement activation in patients with severe COVID-19. Other studies have also reported elevated C5a levels in patients with severe and critical disease [ 3 , 4 ] but, to our knowledge, this is the first study to utilize multiple serial samples to track the progression of complement activation throughout the disease course. In addition, by investigating a cohort of maintenance HD patients we were able to obtain samples from a group of patients with mild disease who, if they had not been attending for HD sessions, would likely not have had contact with healthcare services.…”
Section: Discussionmentioning
confidence: 96%
“…Complement is a major component of the innate immune response and elevated levels of plasma C5a, indicating complement C5 activation, have been identified in patients with severe COVID-19 [ 3 , 4 ]. Vasculitis-like lesions in the lungs with fibrin thrombi of small vessels and infiltrates of neutrophils and monocytes have been identified in post-mortem lung tissue from patients with severe COVID-19 [ 5 ].…”
Section: Introductionmentioning
confidence: 99%